2011
DOI: 10.1063/1.3672685
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluid heat capacities

Abstract: Significant increases in the heat capacity of heat transfer fluids are needed not only to reduce the costs of liquid heating and cooling processes, but also to bring clean energy producing technologies like concentrating solar power (CSP) to price parity with conventional energy generation. It has been postulated that nanofluids could have higher heat capacities than conventional fluids. In this work, nano- and micron-sized particles were added to five base fluids (poly-α olefin, mineral oil, ethylene glycol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…Some nanofluids exhibit anomalous behavior with volume concentration. Starace et al [48] reported both decrease and increase in specific heat capacity for SiO 2 nanoparticles in EG base fluid. Shahrul et al [49] performed comparative review on specific heat of nanofluids for energy applications.…”
Section: Specific Heat Capacitymentioning
confidence: 97%
“…Some nanofluids exhibit anomalous behavior with volume concentration. Starace et al [48] reported both decrease and increase in specific heat capacity for SiO 2 nanoparticles in EG base fluid. Shahrul et al [49] performed comparative review on specific heat of nanofluids for energy applications.…”
Section: Specific Heat Capacitymentioning
confidence: 97%
“…DSC technique has been successfully implemented in a large number of nanofluid studies [172][173][174][175][176][177][178]. Alternatively, some researchers suggested their own experimental setups for measuring c p of nanofluids [8,179,180].…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…For extended reviews regarding the typical nanofluids specific heat capacity, the reader is delegated to references [175,179,190,192].…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…However, only few of them are focused on the influence of nanoparticles on the density and heat capacity of base fluids [4][5][6][7][8][9][10][11][12][13]. Nevertheless, experimental data on the value of the excess functions for these properties provide valuable information about the structure of nanofluid and its nature as a function of the temperature and concentration of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous publication are devoted to different thermophysical and electrokinetic properties of nanofluids [1][2][3][4][5][6][7][8][9][10][11][12][13]. However, only few of them are focused on the influence of nanoparticles on the density and heat capacity of base fluids [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%